1972
DOI: 10.1017/s0033583500000032
|View full text |Cite
|
Sign up to set email alerts
|

The peripheral auditory apparatus

Abstract: This review of the peripheral auditory apparatus represents an attempt to analyse critically recent developments in the field. The coverage is not exhaustive, the emphasis is on functional aspects and no attempt is made to review the anatomy of the ear. Particular emphasis is placed on three broad sections: the physiology of the middle ear, basilar membrane mechanics and the electrophysiology of the cochlea. It is in these areas that recent technical advances have led to experiments which throw doubt on tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
4

Year Published

1976
1976
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(27 citation statements)
references
References 124 publications
0
23
0
4
Order By: Relevance
“…Nearly three decades ago, Johnstone and Sellick (Johnstone and Sellick, 1972) marshalled convincing evidence against the then prevailing view (e.g., Dallos, 1973;Møller, 1963Møller, , 1965Mundie, 1963;Zwislocki, 1962Zwislocki, , 1963 that mass is the principal determinant of ossicular vibrations at high frequencies (see also Manley and Johnstone, 1974). Nevertheless, several subsequent discussions of middle-ear function have reiterated the mass-reactance hypothesis (e.g., Doan et al, 1996;Hemilä et al, 1995Hemilä et al, , 2001Nummela, 1997;Relkin, 1988;Relkin and Saunders, 1980;Shaw, 1981).…”
Section: B Does Mass Reactance Control Middle-ear Transmission Of Himentioning
confidence: 99%
“…Nearly three decades ago, Johnstone and Sellick (Johnstone and Sellick, 1972) marshalled convincing evidence against the then prevailing view (e.g., Dallos, 1973;Møller, 1963Møller, , 1965Mundie, 1963;Zwislocki, 1962Zwislocki, , 1963 that mass is the principal determinant of ossicular vibrations at high frequencies (see also Manley and Johnstone, 1974). Nevertheless, several subsequent discussions of middle-ear function have reiterated the mass-reactance hypothesis (e.g., Doan et al, 1996;Hemilä et al, 1995Hemilä et al, , 2001Nummela, 1997;Relkin, 1988;Relkin and Saunders, 1980;Shaw, 1981).…”
Section: B Does Mass Reactance Control Middle-ear Transmission Of Himentioning
confidence: 99%
“…2A. Second, the phase response in the transverse direction is no longer shallow and becomes consistent with traveling-wave motion (41 The major problem with the isolated temporal bone preparation is that the endocochlear potential was -0 mV, meaning that the electrical drive to the hair cells was about half of its normal in vivo value (48,49). The absence of an endocochlear potential might explain the linearity of the responses (50).…”
Section: Resultsmentioning
confidence: 99%
“…They were deprived of food but not water for [11][12][13][14][15][16][17][18] hr prior to study. They were anesthetized with an intraperitoneal injection of DIAL with urethane (0.9 g/kg of body weight).…”
Section: Methodsmentioning
confidence: 99%
“…By a direct stimulatory action on adenylate cyclase [ATP pyrophosphate-lyase (cyclizing), EC 4.6.1.1], cholera toxin produces secretion of isotonic fluid by the gut (11), the action being mimicked by agents that increase cellular cyclic AMP concentrations. Although the molecular mechanisms for fluid absorption and secretion are not known, it has been demonstrated that cyclic AMP can alter membrane permeability (2, 12) as well as membrane electrolyte secretion (4, 7).The stria vascularis is assumed to be the epithelia membrane responsible for the maintenance of the endolymphatic potential (EP) and endolymph secretion into the scala media of the cochlea (13,14).The present study was performed to demonstrate the presence and possible role of cyclic AMP in the stria vascularis by stimulating intracochlear adenylate cyclase with purified cholera toxin. The toxin had a significant effect on endolymph production, although it did not alter either endolymphatic potential or electrolyte composition.…”
mentioning
confidence: 99%
See 1 more Smart Citation